2020
DOI: 10.1136/annrheumdis-2020-219265
|View full text |Cite
|
Sign up to set email alerts
|

Neither earlier nor late tocilizumab improved outcomes in the intensive care unit patients with COVID-19 in a retrospective cohort study

Abstract: Correspondenceearly promise in retrospective studies also failed in a phase III trial in critically ill COVID-19 patients on mechanical ventilation. 12 These trials raise doubts about benefit of IL-6 blockade in COVID-19.In summary, neither earlier TCZ administration in nonintubated ICU patients with severe COVID-19 associated pneumonia nor late infusion after initiation of mechanical ventilation did reduce mortality. Unfortunately, our findings are in line with the preliminary results of phase III trials of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first study reporting characteristics of and outcomes from COVID-19 for patients requiring ICU admission in Egypt. Similar to previous studies from European [ 2 , 3 , 5 , 8 , 10 , 12 , [15] , [16] , [17] , [18] , 21 , 31 , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ], North American [ 4 , 6 , 7 , [24] , [25] , [26] ], and Asian [ 11 , 19 , 20 , 23 , [27] , [28] , [29] , [30] , 44 ] ICUs, more than two-thirds of our patients were male, with a high prevalence of preexisting comorbid conditions. Nonetheless, 23% of patients in our cohort did not have known comorbid conditions, suggesting that severe SARS-Cov-2 infections with a fatal outcome may also occur in otherwise healthy individuals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study reporting characteristics of and outcomes from COVID-19 for patients requiring ICU admission in Egypt. Similar to previous studies from European [ 2 , 3 , 5 , 8 , 10 , 12 , [15] , [16] , [17] , [18] , 21 , 31 , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] ], North American [ 4 , 6 , 7 , [24] , [25] , [26] ], and Asian [ 11 , 19 , 20 , 23 , [27] , [28] , [29] , [30] , 44 ] ICUs, more than two-thirds of our patients were male, with a high prevalence of preexisting comorbid conditions. Nonetheless, 23% of patients in our cohort did not have known comorbid conditions, suggesting that severe SARS-Cov-2 infections with a fatal outcome may also occur in otherwise healthy individuals.…”
Section: Discussionsupporting
confidence: 90%
“…As of December 21, around 75 million infections have been documented around the globe with an overall mortality rate of 2.23% [ 1 ]. Although most patients with SARS-CoV-2 infections have been reported to develop mild to moderate symptoms, patients with severe respiratory insufficiency requiring admission to the intensive care unit (ICU) are at a high risk of major morbidity and subsequently have high mortality rates [ [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Several cohort studies have reported the characteristics of and outcomes from COVID-19 pneumonia in these critically ill patients [ 2 , 4 , 5 , 11 , 12 , 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of patients with favorable response to TCZ therapy in our study was also defined by the absence of major underlying diseases potentially related with a worse outcome, such as active malignancy or the presence of advanced disease with severe respiratory deterioration (as indicated by higher values of CRP or LDH and lower SpO2/FiO2 ratios) (Table 6). Such factors have been previously related with poor outcome (Richardson et al, 2020, Wu et al, 2020, Zhou et al, 2020 and efficacy of TCZ has been shown to be lower in advanced stages of SARS-CoV-2-related ARDS (Moiseev et al, 2020). Age was not an independent risk factor for clinical failure in our cohort probably due to the relatively young population included (only one third over 60 years old).…”
Section: Discussionmentioning
confidence: 49%
“…Sin embargo, y de acuerdo con la literatura, se han observado beneficios considerables en algunos subgrupos poblacionales de pacientes con COVID-19, aun cuando todavía es considerado prematuro obtener mayores conclusiones. [2][3][4][5][6][7] En el documento emitido por la Secretaría de Salud también se expresa que el tocilizumab no debe ser utilizado como una alternativa. En realidad, el tocilizumab no se utiliza como una alternativa, sino como un coadyuvante al uso de esteroides sistémicos.…”
unclassified